The Relevance of KH Abdul Wahab Hasbullah’s Struggle Values in History Learning Based on the Independent Curriculum Pancasila Student Profile - Salsabila, Helminia; Ayundasari, Lutfiah (Postgraduate Program Magister Pendidikan Agama Islam, 2023)
The Pancasila student profile is something that is focused in the independent curriculum. In implementation, the Pancasila student profile cannot be done instantly but requires a habit. One effort that can be made is providing material regarding the value of the struggle of historical figures who can be used as role models. One figure who can be used as a role model by the younger generation in strengthening the profile of Pancasila students is KH. Abdul Wahab Hasbullah. This research uses qualitative methods with a literature study which aims to explore the values of KH. Abdul Wahab Hasbullah's struggle. who is relevant in learning history based on the Pancasila student profile of the independent curriculum. As for this research, the results found that in KH. Abdul Wahab Hasbullah has six characteristics that are relevant to the profile of Pancasila students, namely: 1) Faith, devotion to God Almighty and noble character, 2) global diversity, 3) working together, 4) independence, 5) critical and creative reasoning.